New variants and in silico analyses in GRK1 associated Oguchi disease. Issue 2 (30th November 2020) - Poulter, James A.; Gravett, Molly S. C.; Taylor, Rachel L.; Fujinami, Kaoru; De Zaeytijd, Julie; Bellingham, James; Rehman, Atta Ur; Hayashi, Takaaki; Kondo, Mineo; Rehman, Abdur; Ansar, Muhammad; Donnelly, Dan; et al.
Abstract: Biallelic mutations in G‐Protein coupled receptor kinase 1 (GRK1) cause Oguchi disease, a rare subtype of congenital stationary night blindness (CSNB). The purpose of this study was to identify disease causing GRK1 variants and use in‐depth bioinformatic analyses to evaluate how their impact on protein structure could lead to pathogenicity. Patients' genomic DNA was sequenced by whole genome, whole exome or focused exome sequencing. Disease associated variants, published and novel, were compared to nondisease associated missense variants. The impact of GRK1 missense variants at the protein level were then predicted using a series of computational tools. We identified twelve previously unpublished cases with biallelic disease associated GRK1 variants, including eight novel variants, and reviewed all GRK1 disease associated variants. Further structure‐based scoring revealed a hotspot for missense variants in the kinase domain. In addition, to aid future clinical interpretation, we identified the bioinformatics tools best able to differentiate disease associated from nondisease associated variants. We identified GRK1 variants in Oguchi disease patients and investigated how disease‐causing variants may impede protein function in‐silico. Abstract : In this study, Poulter et al. expand the number of mutations in Rhodopsin Kinase (GRK1), associated with Oguchi disease, from 13 to 21. The authors compare disease associated mutations with likely nonpathogenic variants in a range of bioinformatic prediction software. In silico analyses of the mutations, using a homology model, suggest mutations result in one of three potential mechanisms of disease: loss of protein, loss of kinase function or a failure of prenylation leading to mislocalisation of the protein.